HAK ANAK UNTUK MENDAPATKAN PERLINDUNGAN DARI KEKERASAN DI LINGKUNGAN SEKOLAH - Ikrar, Ega; Wijaya, Andy Usmina (Legal Standing : Jurnal Ilmu Hukum, 2024)
This study aims to analyze the legal protection of children's rights against violence in school environments and the effectiveness of law enforcement measures. Using a normative juridical method with legislative and conceptual approaches, the research examines various data sources, including legislation such as the Child Protection Act, reports on school violence cases, and relevant academic literature. The data were analyzed qualitatively to evaluate the alignment between regulations and their implementation in practice. The findings reveal that although anti-violence policies have been implemented in several schools, their application remains suboptimal, particularly in addressing non-physical violence such as verbal bullying and emotional abuse. A lack of education about children's rights and legal understanding among educators emerges as a major obstacle. Additionally, reporting mechanisms for school violence cases are often ineffective, leaving many incidents unreported or inadequately addressed. The practical implications of this study include the need for regular training for educators on children's rights and violence handling, strengthening accessible reporting systems for students, and enhancing collaboration among schools, families, and the government. The study also recommends revising anti-violence policies to be more comprehensive and responsive to children's needs. By creating a safe and supportive school environment, the protection of children's rights against violence can be ensured, fostering the development of a physically and mentally healthy future generation.